Melaksanakan Pembelajaran Bahasa Inggris Dengan Cara Yang Variatif Dan Kreatif Guna Mendorong Motivasi Belajar Para Siswa - Yulina Tiwery; Dian Sartin Tiwery; Sefanya Sairiltiata (Fakultas Teknik Universitas Cenderawasih, 2023)
This service activity was carried out by several students from the English Language Education Study Program who are the administrators of the Pattimura University-PSDKU Study Program Student Association (HMPS), Southwest Maluku Regency, which was also attended by 3 lecturers. HMPS English Language Education, which is an internal student organization in campus, apart from organizing academic activity programs, HMPS also provides non-academic activity programs. One of them, HMPS has a role in carrying out Community Service activities which are oriented towards the school community through one of the field I programs